Upper and lower set formulas: Restriction and modification of the Dempster-Pawlak formalism - Türkşen, Ismail Burhan (Zielona Góra: Uniwersytet Zielonogórski)
A modification of Dempster?s and Pawlak?s constructs forms a new foundation for the identification of upper and lower sets formulas. Also, in this modified Dempster-Pawlak construct we require that subsets of the power set be restricted to the well-known information granules of the power set.
Keywords: upper and lower set formulas; information granules; Dempster-Pawlak modification; fuzzy canonical formulas